Teaching English Language in Multilevel Classes: Challenges and Solutions (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article explores the specific problems faced when teaching English in multilevel classes, particularly the disparities in students' proficiency, and offer evidence-based strategies to address these challenges. By understanding the root causes of these issues and implementing targeted solutions, teachers can create a more inclusive and effective learning environment.